Bifurcation in deformation behavior of Cu and Ta by accumulative roll-bonding at high temperature. (15th July 2017) - Mungole, Tarang; Mansoor, Bilal; Ayoub, Georges; Field, David P.
Abstract: Cu and Ta are co-deformed at 673 K by the accumulative roll-bonding technique up to 8 passes. At an equivalent von Mises strain ( ɛ vm ) of ~ 2 the deformation is bifurcated into shear accommodated by the 'soft' Cu, and plane-strain by the 'hard-but-ductile' Ta. This is attributed to transitions occurring collectively at ɛ vm ~ 2 in crystallographic texture, partitioning of recovery and recrystallization, and the nature of interfaces as elucidated by orientation relations, Hall-Petch behavior and manifestation of instabilities at higher strain. Graphical abstract: